Role of Illness Perception towards Medicine Adherence in Tuberculosis Patients - Bibi, Sadia; Amina; Ullah, Kalim (Annals of Human and Social Sciences, 2025)
This study assess illness perception and medication adherence among tuberculosis (TB) patients and evaluate their relationship. Illness perception influences coping behaviors and medication adherence, impacting self-care and recovery.A descriptive cross-sectional study was conducted at Jinnah Hospital, Lahore, from March to June 2024, involving 133 TB patients aged 18 years or older on anti-TB treatment for at least one month. Data were collected using the Brief Illness Perception Questionnaire (BIPQ) and Morisky Medication Adherence Scale (MMAS-8) and analyzed using SPSS v25. Participants were predominantly aged 30–39 years (49.6%), single (67.7%), and had moderate illness perception (77.4%). High medication adherence was observed in 64.7%. No significant association was found between illness perception and medication adherence (p = 0.298). Despite high medication adherence, illness perception had no significant impact, indicating a need for targeted strategies to enhance adherence further.